Using Surveillance Data to Estimate Infectious Disease Burden: Opportunities and Challenges. - Hochheiser, Harry; Kumar, Praveen (American Journal of Public Health, 2025)
The article discusses the estimation of infectious disease outbreaks via surveillance data as of 2025. Topics covered include the mechanics of an approach that generated a Bayesian hierarchical model with adjusted estimates from available data, and its applications, limitations and further development. Also noted is the need for open science practices with greater transparency and collaboration to help modelers inform responses to infectious disease outbreaks.